Virtual Cosmetic Chemistry Lab Design for Bilingual STEAM-Based, Disability-Friendly Learning to Enhance Adaptive Skills - Nilna Inayatan Nafiah; Dika Putra Wijaya; Cahya Adidharma; Shefira Salvabila Safitri; Revianti Aisyah Safitri; Fina Kharisma Musallamah; Aura Gitta Zhafirah; Marshya Qurrotul Aini Wibowo; Ulfa Rahmawati; Nani Farida; Sumari Sumari; Danar Danar (Journal of Computing and Smart Ecosystems, 2025)
Digitalization is growing rapidly along with the development of industrial revolution 4.0 and society 5.0. One of these digitalization products is a digital platform. Current advances in educational technology to improve the quality of learning in educational institutions include using PhET (Physics Environment Technologies) which is a type of virtual laboratory. This research aims to produce a development product in the form of a FORCHEM (Formulation Chemistry Learn and Challenge) application in Virtual Laboratory with a bilingual class system on cosmetic chemistry material at high school level. The research method used is RnD to produce certain products and test the effectiveness of these products in relation to scientific literacy, and FORCHEM innovative learning platform is designed in the form of a virtual laboratory-based application with an online bilingual class system which is equipped with several superior features, one of which is the virtual lab feature and SiBi Microteaching in it, in addition to transferring knowledge and implementing it, it also introduces and brings generation Z into entrepreneurship through the creation of cosmetic products. which is carried out and provides character values in the midst of area megatrends, in order to form a golden generation in 2045 through expanding opportunities for access to higher and better quality education. FORCHEM is able to form 4C (Critical Thinking and Problem Solving, Communication, Creative and Innovation, and Collaboration) through scientific literacy, as well as innovative learning platforms that are disability-friendly and sustainable.